Skin and respiratory ill-health attributed to occupational face mask use. (11th June 2022) - Seed, M J; Fowler, K; Byrne, L; Carder, M; Daniels, S; Iskandar, I Y K; Feary, J; Gawkrodger, D J; van Tongeren, M
Abstract: Background: Face mask use in the workplace has become widespread since the onset of the Covid-19 pandemic and has been anecdotally linked to adverse health consequences. Aims: To examine reports of adverse health consequences of occupational face mask use received by The Health and Occupation Research (THOR) network before and after the pandemic onset. Methods: THOR databases were searched to identify all cases of ill-health attributed to 'face mask' or similar suspected causative agent between 1 January 2010 and 30 June 2021. Results: Thirty two cases were identified in total, 18 reported by occupational physicians and 14 by dermatologists. Seventy-five per cent of cases were reported after the pandemic onset and 91% cases were in the health and social care sector. 25 of the 35 (71%) diagnoses were dermatological, the most frequent diagnoses being contact dermatitis (14 cases) and folliculitis/acne (6 cases). Of the seven respiratory diagnoses, four were exacerbation of pre-existing asthma. Conclusions: There is evidence of an abrupt increase in reports of predominantly dermatological ill-health attributed to occupational face mask use since the start of the pandemic. Respiratory presentations have also occurred.